Professional agency in the classroom and burnout among early career teachers in China - E, Liyuan; Toom, Auli; Pietarinen, Janne; Soini, Tiina; Haverinen, Kaisa; Pyhältö, Kirsi (Frontiers in Psychology, 2024)
The aim of the present study is to investigate early career teachers' professional agency in the classroom. In addition, the association between early career teachers' professional agency in the classroom and the burnout they experienced was examined. In this study, 779 early career teachers, teaching in primary and junior secondary schools in China, responded to the study survey in 2021. The Mplus statistical package (version 8.4) was used to conduct the analysis and the data were analysed using structural equation modelling. The results indicated that early career teachers' professional agency in the classroom consists of three elements: motivation, self-efficacy beliefs, and skills to manage new learning, which entails building a collaborative environment by transforming teaching practices and reflection in the classroom. The results also showed that early career teachers' professional agency in the classroom was negatively related to their burnout.